ANALISIS IMPLEMENTASI PENJAMINAN MUTU DI SMA NEGERI 3 KOTA JAMBI - Jonner Simarmata (Universitas Batanghari Jambi, 2015)
Today education is considered as an investment. Hence, parents are very selective in choosing schools for their children. In response with this public attitude, our government i.e. Ministry of Education has issued Regulation No 63 Year 2009 on education quality assurance system to show its high commitment to improving quality of education. This research aims at investigating how education quality assurance system is implemented in SMA N 3 Kota Jambi. The method applied is descriptive-qualitative. Data is collected through interview, observation, and documentation. Data analysis shows that 1) SMA N 3 Kota Jambi implements quality assurance. 2) There are three kinds of quality assurance system implemented in SMA N 3 Kota Jambi – a. Internal quality assurance system, b. External quality assurance, and c. Top-down quality assurance, 3) the system of quality assurance in SMA N 3 Kota Jambi is unsystematic and unplanned, 4) the system of quality assurance in SMA N 3 Kota Jambi is not under a certain unit but run by headmaster and vice-headmasters, 5) Quality assurance in SMA N 3 Kota Jambi mainly relies on external assurance i.e BAN-S/M, 6) Implementation of quality assurance in SMA N 3 Kota Jambi face problems such as teachers’ unawareness of importance of quality culture and lack of authority of school administrator in impplementing quality management. Based on these findings, it is suggested that 1) there is a need for SMA N 3 Kota Jambi to implement quality assurance under a certain operational unit, 2) there is a need for school administrators to be more empowered by implementing school-based management, 3) there is a need for teachers and administrative staff to be educated about importance of quality culture.Keywords: Quality, Quality assurance, Education quality assurance system